Mitral annular disjunction in patients with severe aortic stenosis: Extent and reproducibility of measurements with computed tomography. (2021) - Tsianaka, T.; Matziris, I.; Kobe, A.; Euler, A.; Kuzo, N.; Erhart, L.; Leschka, S.; Manka, R.; Kasel, A.M.; Tanner, F.C.; Alkadhi, H.; Eberhard, M.
Highlights: Mitral annulus disjunction (MAD) is frequent in patients with severe aortic stenosis. Computed tomography enables a highly reproducible assessment of MAD. MAD patients significantly more often have mitral valve prolapse. Abstract: Objectives: To determine with CT the prevalence and extent of mitral annular disjunction (MAD) in patients undergoing transcatheter aortic valve replacement (TAVR) and its association with mitral valve disease and arrhythmia. Methods: We retrospectively evaluated 408 patients (median age, 82 years; 186 females) with severe aortic stenosis undergoing ECG-gated cardiac CT with end-systolic data acquisition. Baseline and follow-up data were collected in the context of a national registry. Two blinded, independent observers evaluated the presence of MAD on multi-planar reformations. Maximum MAD distance (left atrial wall-mitral leaflet junction to left ventricular myocardium) and circumferential extent of MAD were assessed on CT using dedicated post-processing software. Associated mitral valve disease was determined with echocardiography. Results: 7.8 % (32/408) of patients with severe aortic stenosis had MAD. The maximum MAD was 3.5 mm (interquartile range: 3.0–4.0 mm). The circumferential extent of MAD comprised 34 ± 15 % of the posterior and 26 ± 12 % of the entire mitral annulus. Intra- and interobserver agreement for the detection of MAD on CT were excellent (kappa: 0.90 ± 0.02 and 0.92 ± 0.02). Mitral regurgitation (p = 1.00) and severe mitral annular calcification (p = 0.29) were similarly prevalent in MAD and non-MAD patients. Significantly more patients with MAD (6/32; 19 %) had mitral valve prolapse compared to those without (6/376; 2 %; p < 0.001). MAD was not associated with arrhythmia before and after TAVR (p > 0.05). Conclusions: Using CT, MAD was found in 7.8 % of patients with severe aortic stenosis, with a higher prevalence in patients with mitral valve prolapse. We found no association of MAD with arrhythmia before or after TAVR.